Study on biocharacteristics and puruvate production of moderately halophilic bacteria isolated from dunalliella tertiolecta’s culture medium - Lan Anh, Hoang Thi; Tam, Luu Thi; Hong, Dang Diem (Academia Journal of Biology, 2018)
Moderately halophilic bacteria designed strain D34 was isolated from the culture medium of green microalga Dunaliella tertiolecta. The isolate was Gram-negative, aerobic, rod-shaped, approximately 0.45–0.60 mm wide and 1.25–5.10 mm long, occurring singly, non-motile, and flagellum-less. Colonies on solid media are cream, circular, and smooth. This strain was able to produce exopolysaccharide, poly hydroxybutyrate, oxidase and catalase positive. Growth occurred in a temperature range of 20–40°C, a salt concentration of 0.1–25% (w/v), and pH range 6–12. The major fatty acids were C16:0 (35.59%), C16:1w-7 (20.54%), C18: 1w-7 (30.14%), and C12:0 (10.03% of total fatty acids). Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain D34 belonged to the genus Halomonas. The highest levels of 16S rRNA gene sequence similarity were found between the strain D34 and H. aquamarina (sequence similarity 98.6%). Pyruvate, a central intermediate in metabolism processes in all organisms, is widely used for the synthesis of various chemicals and polymers as well as ingredient or additive in food, cosmetics, and pharmaceuticals. In this study, pyruvate production by strain D34 following changes in culture medium, glucose and nitrate concentrations and culture temperature were also studied. In 84 hours of batch cultivation, pyruvate production by wild-type Halomonas sp. D34 reached 37.24 g/L at 37°C with 20% glucose and 30 g/L sodium nitrate adding to SOT medium. These data provided evidences for pyruvate production using novel wild-type strains.